CD4+ T-Cell Count at Antiretroviral Therapy Initiation in the "Treat-All" Era in Rural South Africa: An Interrupted Time Series Analysis. (26th July 2021) - Yapa, H Manisha; Kim, Hae-Young; Petoumenos, Kathy; Post, Frank A; Jiamsakul, Awachana; De Neve, Jan-Walter; Tanser, Frank; Iwuji, Collins; Baisley, Kathy; Shahmanesh, Maryam; Pillay, Deenan; Siedner, Mark J; et al.
Abstract: Background: South Africa implemented universal test and treat (UTT) in September 2016 in an effort to encourage earlier initiation of antiretroviral therapy (ART). Methods: We therefore conducted an interrupted time series (ITS) analysis to assess the impact of UTT on mean CD4 count at ART initiation among adults aged ≥16 years attending 17 public sector primary care clinics in rural South Africa, between July 2014 and March 2019. Results: Among 20 599 individuals (69% women), CD4 counts were available for 74%. Mean CD4 at ART initiation increased from 317.1 cells/μL (95% confidence interval [CI], 308.6 to 325.6) 1 to 8 months prior to UTT to 421.0 cells/μL (95% CI, 413.0 to 429.0) 1 to 12 months after UTT, including an immediate increase of 124.2 cells/μL (95% CI, 102.2 to 146.1). However, mean CD4 count subsequently fell to 389.5 cells/μL (95% CI, 381.8 to 397.1) 13 to 30 months after UTT but remained above pre-UTT levels. Men initiated ART at lower CD4 counts than women (–118.2 cells/μL, 95% CI, –125.5 to –111.0) throughout the study. Conclusions: Although UTT led to an immediate increase in CD4 count at ART initiation in this rural community, the long-term effects were modest. More efforts are needed to increase initiation of ART early in those living with human immunodeficiency virus, particularly men. Abstract : Universal test and treat (UTT) elicited an immediate increase in CD4 count at antiretroviral therapy (ART) initiation in rural South Africa, with modest long-term effects. Men initiated ART at lower CD4 counts than women. UTT must be combined with other interventions to sustain early ART initiation.